Amal Usaha Aisyiyah Bidang Kesehatan Daerah Padang Pariaman (1978-1998) - Ricky Alviano; Nur`aeni Marta; Abrar Abrar (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Abstract.This study aims to describe Aisyiyah's role in the health sector in the Padang Pariaman area (1978-1998). This study uses historical methods consisting of heuristics, source criticism, interpretation and historiography. Aisyiyah is an autonomous women's organization Muhammadiyah which was founded in 1917 with the initial name Sopo Tresno. Aisyiyah's existence is very helpful in the midst of society because Aisyiyah's organization operates and its programs are in various fields such as health, education, social welfare, and religion/tabligh. The work programs that exist in Aisyiyah in various fields are used as a charitable business organization by building facilities in various fields in accordance with the goals and mission of the Aisyiyah organization. Aisyiyah itself as a Muhammadiyah women's organization often helps the community as a manifestation of the real Aisyiyah movement, in its implementation and being able to realize it by starting the construction of the RBA (Children's Maternity Home) in 1978 which was spearheaded by Syarifah Dinar as chairman of the regional leadership of Aisyiyah Padang Pariaman. In the first year, many patients gave birth at RBA because there were not many midwives at that time. When there was a change in management, RBA experienced a decrease in patients because there were already many village midwives in the Padang Pariaman. Abstrak Penelitian ini bertujuan untuk mendeskripsikan tentang peranan Aisyiyah dalam bidang kesehatan di daerah Padang Pariaman (1978-1998). Penelitian ini menggunakan metode sejarah yang terdiri dari Heuristik, kritik sumber, interpretasi dan historiografi. Aisyiy ah merupakan organisasi otonom perempuan Muhammadiyah yang berdiri tahun 1917 dengan awal nama Sopo Tresno. Keberadaan Aisyiyah sangat membantu di tengah-tengah masyarakat karena organisasi Aisyiyah bergerak dan programnya di berbagai bidang seperti bidang kesehatan, pendidikan, kesejahteraan sosial, dan agama/tabligh. Program kerja yang ada di Aisyiyah diberbagai bidang dijadikan sebagai amal usaha organisasi dengan pembangunan fasilitas diberbagai bidang sesuai dengan tujuan dan misi organisasi Aisyiyah. Aisyiyah sendiri sebagai organisasi perempuan nya Muhammadiyah sering membantu masyarakat sebagai wujud gerakan nyata Aisyiyah, dalam implementasinya serta mampu mewujudkan dengan dimulai adanya pembangunan RBA (Rumah Bersalin Anak) pada tahun 1978 yang dipelopori oleh Syarifah Dinar selaku ketua pimpinan daerah Aisyiyah Padang Pariaman. Tahun pertama banyak pasien yang bersalin di RBA dikarena bidan pada masa itu tidak banyak, Saat terjadi pergantian kepengurusan RBA mengalami penurunan pasien yang disebabkan sudah banyak bidan desa yang ada didaerah Padang Pariaman.